The Effect of Live Video Streaming and e-WOM on Purchasing Decisions of Tik Tok Fashion Consumers with Trust as a Mediating Variable in Pekanbaru - Rahman, M Aldi; Nursanti, Aida; Musfar, Tengku Firli (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
This study aims to determine the effect of Live Video Streaming and Electronic Word of Mouth (e-WOM) on Purchasing Decisions with Trust as a mediating variable for Tik Tok users in Pekanbaru. The study used path analysis with SPSS 25 testing tools. The number of samples in the study was 112 respondents with a purposive sampling method. Data collection was carried out by distributing questionnaires to respondents with criteria, namely being over 17 years old, having purchased fashion products in the Tik Tok application, and having watched live video streaming and carried out e-WOM activities. The results of this study are Live Video Streaming, Electronic Word of Mouth, and Trust have a significant direct influence on Purchase Decisions. However, Trust is not able to be a mediation variable for Live Video Streaming and Electronic Word Mouth (e-WOM) variables on Purchase Decisions.